Optimization of material selection and thickness for crashworthiness of side doors of cars - Lilehkoohi, Ali Hassanzadeh (2016)
Prediction of a conceptual car’s crashworthiness and testing its safety, as well as testing the effect of variables on the safety, has not proved practical to date. While a vehicle is still at the design stage and has not yet been manufactured, it is not possible to conduct a crash test. Nevertheless, as manufacturing of one individual component of the car requires up to five sets of dies, in order to find the best material and thickness for the car body, a new set of dies will be required for each change, which is both expensive and time consuming. The aim of this research is to develop a method for determining the star rating of a Malaysian car using a computer and also to study the effect of variables on car crashworthiness. The first objective is to determine crashworthiness for side doors and the B-pillar of a conceptual vehicle body in Euro-NCAP side and pole side impact tests. The second objective of this research is to determine the effect of material and thickness on crashworthiness of side doors and B-pillars in Euro-NCAP side impact test and pole side impact test. The third objective will focus on developing a mathematical modelling of HIC to predict and calculate it in side and pole side impact tests by assigning various materials and thicknesses to the side doors and B-pillar. The fourth objective of this research is to develop a mathematical model of internal energy to predict and calculate it in side and pole side impact tests by assigning various materials and thicknesses to the side doors and B-pillar. The main goal of this research is to analyse crash criteria and multi-objective optimisation to propose a proper material and thickness for each side door and B-pillar in order to achieve maximum absorbed energy, minimum weight and thus a higher star rated car. The methodology of this study was to conduct simulation tests of the conceptual vehicle. A model of the vehicle, a Moving Deformable Barrier (MDB) and a rigid pole were designed, and this was followed by assigning all initial conditions defined in Euro-NCAP. Car crash simulation using LS-DYNA was conducted to determine the crashworthiness of side doors and B-pillars for side impact tests and then for pole side impact tests, to address objective number one. Four materials including Steel AISI 1006, Aluminum Alloy 5182, Magnesium AZ31B and High Strength Steel 204M with five distinct thicknesses including 0.65, 0.75, 1.0, 1.2 and 1.4mm were assigned to the side doors and B-pillar to investigate the effect of material and thickness on crashworthiness and crash simulations were conducted for both side impact and pole side impact to achieve objective number two. For each conducted simulation, Head Injury Criteria (HIC) and Internal Energy of the side doors and B-pillar were determined from LS-DYNA post processing and then two equations were generated for HIC and Internal Energy as a function of the effective variables. Data analysis and multi-objective optimisation, considering all pertinent variables, was carried out to propose a material and a thickness for the highest absorbed energy with the lowest HIC to achieve objective number three. Several materials and thicknesses, in addition to those tested, were assigned to the formula of HIC and Internal Energy to predict those that are best and safest for the vehicle body to achieve objective number four. Results of side impact tests when the thickness remains original, 0.75mm, show that the highest absorbed energy is when the material is High Strength Steel 204M, where absorbed energy by rear door is 1e+6j, 1.8e+6j for the front door and 1.5e+6j for the B-pillar. In pole impact tests where the material was original and unchanged, the B-pillar with a thickness of 0.75mm absorbed 25e+3j of energy, the front door with a thickness of 1.4mm absorbed 0.14e+6j of energy and the maximum energy absorbed by the rear door was 0.13e+6j for all various thicknesses. Based on the HIC multi-objective crashworthiness determination assigning various thicknesses and materials to the side doors and B-pillar in side impact tests as well as pole side impact tests, it was clearly demonstrated that to have the lowest HIC, the optimised thickness was 1.1mm while the material was Carbon Fibre Reinforced. The Internal Energy multi-objective crashworthiness determination showed that the very best thickness and material for the vehicle body in side impact tests as well as pole side impact tests is Titanium with the thickness of 1.4 mm. In conclusion, as this research was conducted on the side doors and B-pillars only and each material or thickness was assigned to all these three components together, it can be concluded that Carbon Fibre Reinforced with a thickness of 1.1mm is the best option for the safest and highest star rated car for this specific Malaysian local car. Titanium is not a viable option as it is expensive and there are also issues in relation to manufacturing the car body, especially when the thickness is 1.4mm.